Legal Issues of Artificial Intelligence – Generated Works: Challenges on Indonesian Copyright Law - Mayana, Ranti Fauza; Santika, Tisni; Win, Yin Yin; Matalam, Jamil Adrian Khalil; Ramli, Ahmad M (LAW REFORM, 2024)
Digital transformation fosters the massive utilization of Artificial Intelligence (AI) in creating literary, artistic, and musical works worldwide, including in Indonesia. The autonomous functioning of AI challenges the essential presumption that technology is merely a device in the hands of humans in the creation process of Works. This paper examines several legal issues and problems concerning the copyright-ability, authorship, and ownership of AI-generated works using a juridical normative approach. The result of the analysis shows that although the framework of Indonesia's copyright law is based on the principle of human authorship, the rapid development of AI must be balanced with an accommodating legal framework. In conclusion, the Indonesian government can open up the possibility of accepting AI's role in the creation of the work and formulate the limited artificial legal personhood of AI by granting exclusive rights, copyright protection, moral rights, and economic rights to individuals or groups of individuals who produce AI or whose contribution is required for AI function. This formulation is expected to encourage the utilization of AI also provide legal certainty and solve the problem concerning the lack of legal accountability for AI-generated works. In addition, the advancement of technical and legal support is needed in implementing this provisioning model.